An Analysis of Beliefs among UMP International Students towards English Oral Presentation “Pilot Study" - Benraghda, Abdelmadjid; Zuraina, Ali; Noor Raha, Mohd Radzuan (Penerbit Universiti Malaysia Pahang, 2015)

(untitled)
The current study addresses the issue of beliefs among UMP international university students towards performing oral presentation in English language. The objective of this study is to identify their beliefs on speaking and performing oral presentation in English as foreign language in order to determine what kind of belief of UMP international students do possess. The respondents were 30 male and female students. A survey was used in this study that was adapted from Beliefs About Language Learning Inventory (BALLI) as well as personal demographic background questionnaire. The findings show that the international university students held certain beliefs which would be detrimental to their speaking and performing oral presentation in English language as well